Hannah Arendt and American Loneliness - King, Richard H. (Society (New Brunswick), 2013)
It should come as no surprise that Hannah Arendt was always ambivalent about America. In an early post-war letter to her mentor Karl Jaspers, Arendt reflected on life in America. One thing that stood out was "the fundamental anti-intellectualism (Ungeistigkeit) of the country," not the first or last time she would sound the anti-intellectualism theme. In fact, Arendt assumed that to be an intellectual was by definition to be "in opposition" to the "social conformity" that permeated life in the New World. Yet, she praised the commitment to "freedom" in the United States and noted the way that ethnic pluralism helped protect dissenting opinion. She was also impressed (as Alexis de Tocqueville had been in the 1830s) with the way that Americans "felt responsible for public life in a way that I know of in no European country." Overall, her verdict was that the "fundamental contradiction of the country" lies in the co-existence of "political freedom"(politische Freiheit) with "social servitude (gesellschaftlicher Knechtschaft)." Such a judgement about the conflicting tendencies toward freedom and conformity was to remain at the heart of her thinking about America. Arendt was fascinated by her new home, and wrote to her husband Heinrich Bluecher in the summer of 1945 that she was reading "Shakespeare and de Tocqueville." At the time, the couple seem to have been planning a jointly edited volume of European travel accounts of visits to the United States. In general, she considered the Framers' vision of politics fundamental for a modern kind of republican politics, a chance to begin anew. Shot full of ambivalence about America himself, Tocqueville gave to Arendt a way of talking about the American obsession with the pursuit of private interests rather than concern with the fate of the public world. Indeed, at the heart of the conflict between the political and social that runs throughout Arendt's thought were the warring impulses between the creation of the public world and the pursuit of private interests, especially its contemporary expression, the pursuit of consumer happiness. Adapted from the source document.